An Assessment of the psycho-social impact of COVID-19 in India - KALITA, JAGRITI (The journal of contemporary issues in business and government, 2021)
The COVID-19 pandemic which has crippled the world is more than a health crisis. While the impact of this pandemic differs from one country to the other, it has however created chaos and raised instability in the domestic and global order. The immediate effect of this health related menace can be found on the economy of a country. Due to a halt in the economic activities, the world economy is shrinking at a faster rate. India being the third worst hit nations, has her own share of struggles. The tension alongside her borders has added fuel to the fire of misfortune spread by the ever rising corona virus cases. Keeping in mind the current scenario of India, this paper will focus on the social and psychological impacts of the pandemic on the lives of common people in India. As Aristotle rightly said “Man is by nature a social animal.” Men cannot live in isolation; the society completes the individual. The prevailing social distancing and isolation measures to contain the spread of the virus contrasts with men’s inherent nature of being social and has created a lot many personal and social problems.